(untitled) (Revista Tempo e Argumento, 2016)
This article aims to grasp some aspects of the notion of humanism in photography and its closeness to the political culture and the visual culture in the period, through the specific experiences of George Rodger and Henri Cartier-Bresson, two photographers who were first-hand witnesses and provided accounts of horror in the Nazi concentration camps at the end of World War II. George Rodger photographed the Bergen-Belsen camp as soon as it was liberated by the British troops. Henri Cartier-Bresson was there with a film crew recording the deported masses newly freed from the Nazi concentration and extermination camps. These experiences came to have profound impact on the biography and work of both of them. In the two cases, there is a notion of humanism linked to World War II events, which is observed in photography and photographic representation, and it has a significant consequence for the contemporary visual culture. Keywords: Visual Culture; Political Culture; War Photography; Photojournalism; Concentration Camps. Original title: O humano e o desumano: cultura visual, cultura política e as imagens feitas por George Rodger e Henri Cartier-Bresson nos campos de concentração nazistas.